Breakfast Habits and Nutritional Status of Female Students in an Islamic Boarding School - Aulia, Nurul; Kumalasari, Mei lina Fitri; Nilandita, Widya (International Conference on Sustainable Health Promotion, 2025)
Breakfast was very important as the main source of nutrients needed for the brain to function properly. Adolescents who frequently skipped breakfast were less selective in choosing their food at lunch due to excessive hunger, leading to overeating in the afternoon or evening. This risked them consuming calories exceeding their daily needs, which in the long term could have a negative impact on their health, such as weight gain and the risk of obesity. This research was an analytical observational study using a cross-sectional design. The research was conducted at Islamic Boarding School from October to November 2024. Sampling was done using Simple Random Sampling technique on 44 respondents from a total population of 54. Data collection was carried out by distributing questionnaires to respondents who met the predetermined inclusion and exclusion criteria. The obtained data was analyzed using the Spearman correlation test with a significance level of 5% (p<0.05). The results showed that there was a relationship between breakfast habits and nutritional status among the female students at Islamic Boarding School, with p=0.035 < 0.05. The conclusion of this study was that low, moderate, and high breakfast habits could influence nutritional status. This is because with breakfast, the energy intake entering the body is met, neither too much nor too little.